Divine multiplicity trinities, diversities, and the nature of relation - Boesel, Chris; Ariarajah, S. Wesley; ebrary, Inc. (New York : Fordham University Press, 2014)
"The essays in this volume pose critical questions and suggest constructive possibilities regarding the extent to which trinitarian and pluralist discourses can be put into fruitful conversation with one another. On one hand, the volume interrogates the possibilities of trinitarian theology and its ethical promise with regard to divine and creaturely relationality by putting it into specific engagement with discourses of pluralism, diversity, and multiplicity. It asks how trinitarian conceptions of divine multiplicity might open the Christian tradition to increasingly more creative and affirming visions of creaturely identities, difference, and relationality--including the specific difference of religious plurality. Alternatively, where can the triadic patterning evident in the Christian theological tradition be seen to have always exceeded the boundaries of Christian thought and experience, inhabiting and determining other religious traditions' conceptions of divine and/or creaturely reality in ways internal to their own distinctive histories? On the other hand, the volume interrogates the possibilities of various discourses on pluralism by putting them in a very particular and concrete pluralist context. Religious pluralists, comparative theologians, and scholars of religious studies are place alongside and put into conversation with theological and doctrinal work carried out within the (albeit broadly conceived) normative thread of the Christian trinitarian tradition. To what extent can pluralist discourse collect within itself a convergent diversity of orthodox, heterodox, postcolonial, process, poststructuralist, liberationist, and feminist sensibilities while avoiding irruptions of conflict, competition, or the logic of mutual exclusion? The goal of this collection is that, in the midst of these crisscrossing lines of cohering and/or conflictual difference about the theme of divine multiplicity, critical and imaginative visions of divine and creaturely relations might be generated that can inform future theological, philosophical and ethical work in transdisciplary, inter-religious and intra-religious contexts"--
Machine generated contents note: -- Acknowledgments -- Introduction: The Whence and the Whither of "Divine Multiplicity" / Chris Boesel and S. Wesley Ariarajah -- PART I : PHILOSOPHICAL EXPLORATIONS: DIVINITY, DIVERSITY, DEPTH -- The God Who Is (Not) One: Of Elephants, Blind Men, and Disappearing Tigers / Philip Clayton -- God's Vitality: Creative Tension and the Abyss of Diff erance within the Divine Life / Eric Trozzo -- Polyphilic Pluralism: Becoming Religious Multiplicities / Roland Faber and Catherine Keller -- PART I I : INTERRELIGIOUS EXPLORATIONS: RELIGIOUS DIVERSITY AND DIVINE MULTIPLICITY -- Abhinavagupta's Theogrammatical Topography of the One and the Many / Loriliai Biernacki -- One and the Many: The Struggle to Understand Plurality within the Indian Tradition and Its Implications for the Debate on Religious Plurality Today / S. Wesley Ariarajah -- Diff erential Pluralism and Trinitarian Theologies of Religion / S. Mark Heim -- Spirited Transformations: Pneumatology as a Resource for Comparative Theology / Holly Hillgardner -- PART I I I : THEO-ANTHROPOLOGICAL EXPLORATIONS: QUEER GOD, STRANGE CREATURES, STORIED SPIRIT -- Excess, Reversibility, and Apophasis: Rereading Gender in Feminist Trinities / Sara Rosenau -- Doxological Diversities and Canticle Multiplicities: The Trinitarian Anthropologies of David H. Kelsey and Ivone Gebara / Jacob J. Erickson -- The Holy Spirit, the Story of God / Sam Laurent -- PART I V : DOCTRINAL EXPLORATIONS: TRINITY, CHRISTOLOGY, AND THE QUALITY OF RELATION -- Absolute Diff erence / Kathryn Tanner -- Multiplicity and Christocentric Theology / John F. Hoff meyer -- Divine Relationality and (the Methodological Constraints of ) the Gospel as Piece of News: Tracing the Limits of Trinitarian Ethics / Chris Boesel -- The Universe, Raw: Saying Something about Everything / Cynthia L. Rigby -- Notes -- List of Contributors.
Includes bibliographical references.
Electronic reproduction.
Keywords: Trinity; Christianity and other religions; Electronic books